Trabalhos do parto: a Maternidade Dr. João da Rocha Moreira e o corpo feminino em Fortaleza (1915-1933) - Medeiros, Aline da Silva (2010)
The present work intends to discuss the medical investments which had as target the woman s body, in the capital of Ceará, since the foundation, on March 1915, of the first city s maternity, the Maternity Dr. João Moreira. Divided between the hospital care service and the activities that made up the training of the midwives, the Maternity Dr. João Moreira constituted the productor and propagator center of new ways to understand and deal with the female body in childbirth, which in turn was significantly different from the previous methods of body reading carried by the traditional midwives, who then dominated the scene of the birth in Fortaleza city. The reviewed documentation, consisting of clinical cases, reports and statistical studies, also allowed the analysis of the gradual employment of technical procedures which surrounded the childbirth inside and outside of the Maternity Dr. João Moreira, with particular emphasis on the reorganization of the distances between nature and artifice, and its implications on the gestures professionals dedicated to the female body